Periodicity of Diurnal Variation of Soil Radon Concentration Levels and Temperature - N. M. Ershaidat; R. R. Almomani; B. A. Al-Bataina; W. S. Al-Rayashi (Jordan Journal of Physics, 2025)
Concentration levels of soil radon at various depths (25, 50 and 75 cm), over a period of two days, in a phosphatic formation site located in Irbid, Jordan were measured using an active detector, the RAD7®from Durridge Company, USA. Periodicity of diurnal soil radon concentration levels is observed. Data were fitted using a cosine function. This fit produces a pattern similar to that of the variation of temperature of the soil with time obtained by the solution of the heat equation. The angular frequency of the periodicity is consistent with that of the temporal variation of the temperature of the soil for a given depth. Periodicity is clearly marked for the depths 25 cm and 50 cm, which is consistent with previous studies. Keywords:Soil radon; Heat equation; Diurnal variation, RAD7®; Active detector; Phosphatic formation; Irbid. PACS: 93.85.Np, 29.40.-n, 92.40.Lg